Unraveling the effects of the Ebola experience on behavior choices during COVID-19 in Liberia: a mixed-methods study across successive outbreaks - Laura A. Skrip; Malcom B. Weller; Sheikh Dukuly; Neima Candy; Wahdae-Mai; Adolphus Clarke; Bernice T. Dahn (BMC, 2024)
Abstract Background The burden of the COVID-19 pandemic in terms of morbidity and mortality differentially affected populations. Between and within populations, behavior change was likewise heterogeneous. Factors influencing precautionary behavior adoption during COVID-19 have been associated with multidimensional aspects of risk perception; however, the influence of lived experiences during other recent outbreaks on behavior change during COVID-19 has been less studied. Methods To consider how the direct disease experience ("near misses") and behavior change during the 2014-2016 Ebola virus disease (EVD) outbreak may have impacted behavior change during the early waves of the COVID-19 outbreak in West Africa, we analyzed data from a mixed-methods study that included a phone-based survey and in-depth interviews among vaccinated Liberian adults. Logistic regression via generalized estimating equations with quasi-likelihood information criterion (QIC)-based model selection was conducted to evaluate the influence of the interaction between and individual effects of the outbreak (EVD and COVID-19) and the "near-miss" experience on adoption of individual precautionary behaviors. Thematic analysis of interview transcripts explored reasons for differential behavior adoption between the two outbreaks. Results At the population level, being a "near miss" was not associated with significantly different behavior during COVID-19 versus Ebola; however, overall, people had lower odds of adopting precautionary behaviors during COVID-19 relative to during Ebola. Participants who report near miss experiences during Ebola were significantly more likely to report having a household member test positive for COVID-19 (p<0.001). Qualitatively, participants often reflected on themes around more proximal and personal experiences with Ebola than with COVID-19; they also commented on how EVD led to better preparedness at the systems level and within communities for how to behave during an outbreak, despite such awareness not necessarily translating into action during COVID-19. Conclusions The results suggest that perceived proximity and intensity to disease threats in space and time affect behavioral decisions. For successive disease threats, comparisons of the present outbreak to past outbreaks compound those effects, regardless of whether individuals were directly impacted via a "near-miss" experience. Measures, such as risk communication and community engagement efforts, that gauge and reflect comparisons with previous outbreaks should be considered in response strategies to enhance the adoption of precautionary behavior.